MICROFINANCE, EASTERN EUROPE AND UKRAINE - Abe, Kiyoshi (Journal of European Economy, 2018)
The evolutionary features of developing countries predetermine the need for microfinance as an instrument of poverty eradication. The analysis of microfinance proliferation channels and current situation in Eastern European countries allows the author to determine major obstacles to and perspectives of microfinance network development in Ukraine.